2018
DOI: 10.1103/physrevb.97.224423
|View full text |Cite
|
Sign up to set email alerts
|

Role of fluctuations for density-wave instabilities: Failure of the mean-field description

Abstract: Density-wave instabilities have been observed and studied in a multitude of materials. Most recently, in the context of unconventional superconductors like the iron-based superconductors, they have excited considerable interest. We analyze the fluctuation corrections to the equation of state of the density-wave order parameter for commensurate charge-density waves and spin-density waves due to perfect nesting. For XY magnets, we find that contributions due to longitudinal and transverse fluctuations cancel eac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Another interesting implication of our analysis is with regard to many-body theories that have structural similarities to the BCS theory, such as density-wave instabilities with perfect nesting. In this case, it can be shown that the cancellation of transverse and longitudinal modes is not always guaranteed, leading to important limitations of the mean-field theory of density-wave systems [30]. The diagrammatic representation of the fluctuation corrections to the gap equation (22) along with the discussion of the importance of the different contributions is presented in Ref.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another interesting implication of our analysis is with regard to many-body theories that have structural similarities to the BCS theory, such as density-wave instabilities with perfect nesting. In this case, it can be shown that the cancellation of transverse and longitudinal modes is not always guaranteed, leading to important limitations of the mean-field theory of density-wave systems [30]. The diagrammatic representation of the fluctuation corrections to the gap equation (22) along with the discussion of the importance of the different contributions is presented in Ref.…”
Section: Discussionmentioning
confidence: 99%
“…The diagrammatic representation of the fluctuation corrections to the gap equation (22) along with the discussion of the importance of the different contributions is presented in Ref. 30 for a closely related problem.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 In particular, in the weak coupling limit, the retardation effects are implemented as an ultraviolet cutoff Λ = ω D in the self-consistent calculation of the order parameter. There are known limitations to this line of arguments, 31 but we think that these limitations are not relevant for the 'hidden-order' transition. To summarize, to the best of our knowledge there is no experimental evidence for the retardation effects being observed through the 'hidden order' transition and the emergence of an energy scale (analogous to ω D in the BCS theory) that would be much smaller than the Fermi energy.…”
Section: Discussionmentioning
confidence: 92%
“…The action S fluct describes the effects of quantum fluctuations beyond mean field theory. The consequences of these fluctuations for the thermodynamics of related BCS superconductors have been worked out in detail previously [46][47][48]. Much can be gleaned from these studies for our B = 0 model of the excitonic insulator Eq.…”
mentioning
confidence: 93%
“…This leads to a total free energy Ω(B) that is the sum of mean-field Ω MF (B) and fluctuation Ω fluct (B) contributions. Despite the nonzero magnetic field, the fluctuation free energy can be written in the same form as for B = 0 [46][47][48],…”
mentioning
confidence: 99%